TESTING THREE PROPOSED DNA REGIONS (matK, rbcL and ITS2) FOR IDENTIFICATION OF CAMELLIA EUPHLEBIA AND CAMELLIA CHRYSANTHA - Van Viet, Nguyen; Quang Trung, Pham; Quang Trung, Do; Viet Ha, Tran; Douangmala, Sounthone (Journal of Forestry Science and Technology, 2022)
Camellia sp. is a yellow flower tea species that have high economic values and have been used as a nutritious beverage, medicine and an ornamental plant. The identification of these species are based on morphological characteristics and recently by molecular markers such as matK, ITS2, rbcL. This paper shows that the nucleotide sequenc of three DNA regions (matK, ITS2, rbcL) can be used to identify Camellia sp. collected from different areas in Vietnam (Quang Ninh and Bac Giang).The results also show that those three locations can be amplified by directional PCR. In addition, the nucleotide differences among those DNA regions of the two Camellia species ranged from 0% to 0.82% suggesting the Camellia chrysantha (Ba Che, Quang Ninh) is a derivative of Camellia euphlebia (Son Dong, Bac Giang).